A new class of meta-pyridine-urea oligomers for selective identification of mercury(II) ions. Issue 25 (20th June 2019) - Liu, Yajing; Chi, Chenjing; Wu, Renbo; Huang, Yong; Liu, Song; Sun, Mingyue; Sun, Yuli; Yang, Zequn; Chen, HuaLong; Wu, Zehui
Graphical abstract: Highlights: A series of new pyridine-urea oligomers were synthesized. A new highly selective probe for the detection of Hg 2+ in PBS buffer. DFT calculations were used to optimize the structures ofL1-6 and its Hg 2+ complex. Possible mechanism for Hg 2+ recognition process is the intramolecular charge transfer. Abstract: A series of new pyridine-urea oligomers were synthesized and tested for their ability to recognize ions in PBS or Ac buffer solution by fluorescence. The results showed that the ability of oligourea urea to selectively recognize Hg 2+ was gradually enhanced with the increase of chain, which was further proved by DFT calculation. The 1:2 stoichiometry was established for theL7 -Hg 2+ complex on the basis of Job's plot. The binding constant ( K B ) and the lowest detection limit for Hg 2+ were also determined. DFT calculations were used to optimize the structures ofL2-7 and its Hg 2+ complexes. Highly sensitive and selective probes for the recognition of Hg 2+ based on this report are expected to be developed and used for in vivo detection.